The relationship between perceived employability, core self-evaluations, and approach-avoidance temperaments in South African University students - Griffin, Rebecca (Organisational Psychology, 2025)
Over the last two decades, traditional perspectives on employability have shifted because of changes in the labour market (e.g., technological advancements, the massification of higher education, and rising unemployment). Employability is now contingent on more factors than qualifications alone, and individuals' perceptions of employability depend on a range of psychosocial factors that relate to their personal identity or self-beliefs. In order to shed light upon how job seekers' core self-evaluations, defined as individuals' general self-perceptions, may impact their self-perceived employability, this study adopts an approach-avoidance framework to identify how individual difference factors may explain individuals' employability perceptions. This cross-sectional study collected survey response data from 303 South African prospective job seekers. Correlation analysis revealed that perceived employability and core self-evaluations were positively related, suggesting that general evaluations of self-worth may affect how individuals perceive their own employability. Likewise, perceived employability was related to job seekers' approach-avoidance temperaments. Mediation analyses suggested that perceived employability may be influenced by approach-avoidance temperaments through core self-evaluations as an intermediary mechanism. This study contributes to theory by identifying antecedents of perceived employability, exploring mechanisms underlying employability perceptions, and highlighting the utility of the approach-avoidance framework in understanding perceived employability. Practical implications and avenues for future research are discussed.